2013
DOI: 10.4236/jdm.2013.31002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family history of diabetes on sleep quality, depression, and anxiety in adult males with diabetes

Abstract: Study Objectives: This study evaluated how a family history of diabetes moderates the effects of diabetes on anxiety, depression, as well as sleep quality. Design: Outpatients with diabetes responded to questionnaires on family history of diabetes, sleep quality, anxiety and depression. Participants: Participants were recruited from the Captain James A. Lovell Federal Health Care Center in North Chicago, Illinois. All participants were adult males (n = 33) with ages ranging from 50 to 88 and were diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A previous study suggested that an increase in knowledge concerning diabetes care could relieve symptoms of anxiety and depression [ 69 ]. A positive family setting provides an opportunity for a patient to obtain personal experience in chronic disease management and consequently manage his/her own disease more effectively [ 70 ]. Another protective factor against the presence of depression symptoms was the high social support level in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that an increase in knowledge concerning diabetes care could relieve symptoms of anxiety and depression [ 69 ]. A positive family setting provides an opportunity for a patient to obtain personal experience in chronic disease management and consequently manage his/her own disease more effectively [ 70 ]. Another protective factor against the presence of depression symptoms was the high social support level in this study.…”
Section: Discussionmentioning
confidence: 99%